Matching Cost Against Revenue at Royalty Expenses - Muhammad Rifky Santoso (The Indonesian Accounting Review, 2021)
The recording of royalty expenses must not only be consistent but also complied with the principle of matching costs against revenue, especially in calculating taxable income. If all accounting principles are not met in recording the royalty expense, the tax authority will correct it  so that the royalty expenses cannot be deducted from taxable income. By using a case in a tax court in Indonesia, there is a taxpayer who does not meet the matching cost against revenue principle when recording royalty expenses. The taxpayer deducts these royalty expenses for the previous year in the current year because the amounts of these royalty expenses are known exactly in the current year. Even though the taxpayer's financial statements were audited and had an unqualified opinion, the Directorate General of Taxes (DGT) as the tax authority in Indonesia negated the royalty expenses as a deduction from taxable income. This paper finds that a net sales-based royalty fee scheme can be estimated at the end of the year and deducted from gross income without waiting for a certainty on the amount of royalty expense on invoices received in the coming year. The accounting records of the taxpayer are not proper so that some data or documents cannot be proven in the tax court. The method of recording in the financial statements with an unqualified opinion does not guarantee that the recording follows tax regulations, especially following Generally Accepted Accounting Principles (GAAP).